Aspek Hukum Dalam Penerapan Prinsip Know Your Customer (KYC) Pada Lembaga Perbankan - Silalahi, Bob Ben Salomoan; B, Baidhowi; Novita, Yustina Dhian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In facing the challenges of globalization and increasing financial crimes such as money laundering and terrorism financing, the Know Your Customer (KYC) principle is an important pillar in maintaining the integrity of the financial system in Indonesia. This article analyzes the legal aspects of the application of the KYC principle in Indonesian banking institutions using a normative legal approach. The study was conducted on various regulations that serve as the legal basis, including Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering, as well as regulations from the Financial Services Authority and Bank Indonesia. The findings show that although the legal framework is available and the implementation of KYC has made a significant contribution to identifying and preventing suspicious transactions, there are still implementation challenges such as limited human resources, technology gaps, and ownership of official documents by customers. To increase the effectiveness of KYC, it is necessary to increase human resource capacity, utilize advanced technology, and strengthen cross-country cooperation in combating financial crimes.